Beyond imagination: an alternative cruelty in Samuel Beckett's drama - Chin, Eunice Shi Xian (Nanyang Technological University, 2024)
The sensorial experience is a significant element in Samuel Beckett’s works and has led to much scholarship being done on it, with many of them particularly focusing on embodiment/disembodiment, absence/presence, and silence/sound. When discussing the spectator’s sensorial experience, a notable piece of work is Antonin Artaud’s concept of the Theater of Cruelty, created “in order to restore an impassioned convulsive concept of life” (Artaud 81). Cruelty here refers to a sensory disruption – a pure, detached and implacable feeling exercised in the torture and trampling down of everything (114) – using explicit and intense gestures, sounds and images to shock the spectator. It can thus be said that Artaudian cruelty works because the images presented go against the familiar to provoke such discomfort. However, I propose that Beckett’s dramatic works, specifically his radio plays, demonstrate how the same can also be achieved through the opposite. Compared to Artaudian cruelty, the cruelty created in Beckett’s works draws upon the minimal to provoke the same effects. This approach could possibly be more effective as there are no pre-existing images for the mind to use as a reference, relying purely on sensation. Beckett’s works often rely on the unseen and unsaid, thus creating a negative space where the imagination is activated, and intuition is heightened. This thesis will therefore argue for an alternative cruelty that goes beyond the Artaudian form. It creates a sensorial experience that ultimately guides us towards an intuitive mode of spectating. Here, we are pushed to our limits to a “pure, detached and implacable feeling” (114), and towards a lived reality beyond epistemological structures when absence can mean more than presence, and where we can aspire towards an unmediated access to experience.